Shariah Framework Based on Qualities of Shariah Scholars Towards Islamic Fatwa Shopping in Nigeria - Yakasai, Umar Musa; Muhamad, Tijjani (Institut Agama Islam Negeri Ponorogo, 2023)
This study examines the characteristics of Islamic scholars in issuing fatwas, highlighting concerns that financial institutions may seek fatwas aligning with their profit-driven motives, potentially contradicting Islamic principles. Focusing on Nigeria, it assesses the qualifications of advisors and supervisors in Islamic financial institutions and examines their link to the issuance of fatwas. Gathering insights from 250 randomly selected Shariah scholars and students, the research employs structural equation modeling (SEM) for analysis. The reliability of survey responses was assessed using a 5-point Likert scale. The consistency of the data was verified using mean-variance extracted, composite reliability, and Cronbach's alpha. SEM was used to assess the relationship between scholars' qualifications and the issuance of fatwas. The results underscore the importance of attributes such as knowledge, piety, sincerity, honesty, and legal responsibility in the issuance of fatwas, reflecting broader concerns about fatwa shopping. The study's scope was limited to Nigeria, focusing on scholars' perceptions of fatwa shopping